Enhancing the activity and stability of cadmium zinc sulfide photocatalyst for hydrogen production from water - Leni Yuliati, Leni Yuliati (2015)
Hydrogen is still considered as one of the cleanest energy to date. In order to achieve a sustainable process for the hydrogen production, photocatalytic water splitting to produce hydrogen would be a suitable approach . However, due to the low efficiency and lack of stability, the developments of active and stable photocatalysts, especially those that can work under visible light irradiation are still highly required . On the other hand, cadmium zinc sulfide has been recognized as an active visible light-driven photocatalyst for hydrogen production . Unfortunately, the cadmium zinc sulfide is usually not stable. In order to enhance not only the activity but also the stability of the cadmium zinc sulfide photocatalyst, various modifications were carried out by addition of tin, copper, or silver via hydrothermal and co-precipitation methods [1-3] . It was demonstrated that the hydrothermal method was better than the co-precipitation method to prepare the modified cadmium zinc sulfide photocatalysts. The addition of optimum amount of tin, copper, or silver by hydrothermal method successfully improved both activity and stability of the cadmium zinc sulfide photocatalyst for hydrogen production under visible light irradiation. several reasons were proposed for such enhancements, which were high crystallinity, good absorption at visible light region (narrow band gap energy), and suppression of electron -hole recombination.